Pengaruh Prinsip Bagi Hasil dan Bunga, Reputasi Bank, dan Asimetri Informasi Terhadap Keputusan Nasabah dalam Memilih Jasa Perbankan: Bank Syariah dan Bank Konvensional di Kota Jambi - Eka Julianti E.S; Sri Rahayu; Ilham Wahyudi (Jurnal Akuntansi & Keuangan Unja, 2018)
This study was intended to examine the effect of profit sharing principle and interest, bank reputation, and information asymmetry against customer decision in choosing banking services, that is between islamic bank and conventional bank in Jambi City. Data in this study is primary data by using questionnaire. The sample selection in this research used nonprobability sampling technique with acidental sampling technique. The sample obtained in this study were customer of islamic bank and customer of conventional bank in Jambi City. The analysis method used was discriminant analysis using IBM SPSS Statistic 22. The results of the discriminant analysis prove that in choosing banking services in Jambi City between islamic banks and conventional banks, customers do not see from the principle of profit sharing and interest, bank reputation and information asymmetry. Keywords: Islamic Bank, Conventional Bank, Profit Sharing, Reputation, Information Asymmetry